Occurrence, dietary exposure, and health risk estimation of polycyclic aromatic hydrocarbons in grilled and fried meats in Shandong of China. Issue 8 (16th October 2018) - Jiang, Dafeng; Wang, Guoling; Li, Linlin; Wang, Xiaolin; Li, Wei; Li, Xia; Shao, Lijun; Li, Fenghua
Abstract: There is a lack of information regarding the quantitative determination and health risk assessment of polycyclic aromatic hydrocarbons (PAHs) in grilled and fried meat products in Shandong Province of China. The aim of this work was firstly to detect the contamination levels of 15 PAHs in 52 grilled and fried meats consumed by the population of Shandong Province, China. In brief, concentrations of the sum of 15 PAHs in individual samples were ranged from 8.23 to 341 μg/kg with a mean contamination level of 63.3 μg/kg. Moreover, the factors for the formation of PAHs in these samples have been identified and analyzed. One grilled meat sample exceeded the maximum limits of 2 and 12 μg/kg set for BaP and PAH4 by the European Union. For a further step, the mean dietary exposures for total PAHs from grilled and fried meat products were estimated to be 120 and 74.8 ng/kg bw/day, respectively. Finally, the health risk estimation was performed using the incremental lifetime cancer risk (ILCR) approach. The obtained values of four groups were all lower than 10‐4, indicating a slight potential carcinogenic risk of consumer health. This study was the first attempt to provide baseline information of potential health risk of dietary exposure of PAH‐containing grilled and fried meats, which could be useful for health management of the local consumers. Abstract : The contents of this page will be used as part of the graphical abstract of html only. It will not be published as part of main article